# Polynomial factorisation

#### lookagain

##### Elite Member
Robegk, I got this:

$$\displaystyle (x - y)^2 \ + \ 3(y - x)^3 \ =$$

$$\displaystyle (x - y)^2 \ - \ 3(x - y)^3 \ =$$

$$\displaystyle (x - y)^2[1 - 3(x - y)] \ =$$

$$\displaystyle (x - y)^2(1 - 3x + 3y) \ =$$

$$\displaystyle (x - y)^2(-3x + 3y + 1)$$

___________________________

What did you get?

#### Robegk

##### New member
Robegk, I got this:

$$\displaystyle (x - y)^2 \ + \ 3(y - x)^3 \ =$$

$$\displaystyle (x - y)^2 \ - \ 3(x - y)^3 \ =$$

$$\displaystyle (x - y)^2[1 - 3(x - y)] \ =$$

$$\displaystyle (x - y)^2(1 - 3x + 3y) \ =$$

$$\displaystyle (x - y)^2(-3x + 3y + 1)$$

___________________________

What did you get?
Thank you for the detailed reply, can I ask you on step 3 of your workings where the 1 comes from, I can't understand it, sorry

#### Otis

##### Elite Member
where the 1 comes from
Hi Robegk. He factored out the expression (x-y)^2. Like this pattern:

z^2 - 3z^3 = z^2(1 - 3z)

If you're still puzzling over it, then use the distributive property to multiply out (expand) the right-hand side. Do that twice, with the 1 and without the 1, and see what happens. #### Robegk

##### New member
Now I understand! Thank you very much for your help people, much appreciated  